Issues of Time Change Forecasting of the Total Delay of GPS Signals - Eminov, R.A. (Herald of Azerbaijan Engineering Academy, 2022)
A normalized mathematical model of tropospheric refractivity is proposed. An analytical expression is obtained for calculating the quantity of the partial pressure of water vapor, at which the total delay reaches a minimum value. On the basis of the available factual material, an experimental confirmation of the presence of a minimum of the total tropospheric delay predicted due to the proposed model is found.